Hubungan antara Budaya Organisasi dengan Kinerja Guru SD Metta Maitreya Pekanbaru - Yadi Sutikno; Sonika Sonika; Rida Jelita (Jurnal Maitreyawira, 2021)
This research is background by the performance of teachers at SD Metta Maitreya who are still not professional, there are still scores of students who take KKM and there are still teachers who lack teacher responsibility at work. Therefore, this study aims to determine the relationship between organizational culture and teacher performance at SD Metta Maitreya Pekanbaru. The research method used is a survey method with correlational techniques. The study population was 24 teachers of SD Metta Maitreya Pekanbaru, so the sample was 24 people. The data collection instrument was in the form of a questionnaire or questionnaire. The validity and reliability of the performance questionnaire and organizational culture have been tested. The data normality test was carried out by the Kolmogorov Smirnov test. The data analysis used was multiple correlation analysis with a level of α = 0.05. The results of data analysis show that there is a significant relationship between Organizational Culture (X1) and Teacher Performance (Y) together with the regression equation Y = 102.421 + 0.567X1 with a correlation coefficient of 0.567. The results of this study are expected to be useful for improving the performance and organizational learning of SD Metta Maitreya Pekanbaru. The conclusion of this study shows that organizational learning (X1) has a partially significant relationship (individually) with teacher performance (Y) SD Metta Maitreya.